2014
DOI: 10.1088/0022-3727/47/38/385301
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of thermal decomposition processes and associated damage in carbon fibre composites

Abstract: Abstract.Thermo-chemical degradation of Carbon Fibre Composite materials (CFCs) under intensive heat fluxes has been modelled. The model couples together heat diffusion, polymer pyrolysis with associated gas production and convection through partially decomposed CFCs, and changes in transport properties of the material due to the damage. The model has been verified by laser ablation experiments with controlled heat input. The numerical predictions indicate that the thermal gas transport has a minimal affect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 20 publications
(30 reference statements)
1
26
0
Order By: Relevance
“…The thermal properties of the three phases provided by [25,26] are given in Table 2. Due to the elastic brittle behavior of CFRP, the heat generated by plastic deformation is negligible and the unique heat source taken into account in the model was produced by the friction at the contact surface between the tool and workpiece.…”
Section: Fe Modeling Of Fiber-reinforced Polymer Composites 31 Descrmentioning
confidence: 99%
“…The thermal properties of the three phases provided by [25,26] are given in Table 2. Due to the elastic brittle behavior of CFRP, the heat generated by plastic deformation is negligible and the unique heat source taken into account in the model was produced by the friction at the contact surface between the tool and workpiece.…”
Section: Fe Modeling Of Fiber-reinforced Polymer Composites 31 Descrmentioning
confidence: 99%
“…This numerical model, which was mainly based on the model by Chippendale et al [24], considered the processes of the thermal transport, the polymer degradation, the pyrolysis gases transport, and the carbon fiber sublimation in the composite. The model formulations [2436] and the calculation parameters [18,24,29] Figure 8 shows the temperature field and the internal gas pressure distribution in the composite along the thickness direction with a laser irradiation time of 1 ms (1 pulse duration). From the temperature profiles of Figure 8, it could be found that a higher laser peak power density led to a faster temperature rise and a faster heat transfer in the composite.…”
Section: Simulation Of the Internal Gas Pressurementioning
confidence: 99%
“…To prove the speculation, a two-dimensional axisymmetric finite element model was established in order to predict the temperature field and the internal gas pressure in the composite during the laser drilling. This numerical model, which was mainly based on the model by Chippendale et al [24], considered the processes of the thermal transport, the polymer degradation, the pyrolysis gases transport, and the carbon fiber sublimation in the composite. The model formulations [24][25][26][27][28][29][30][31][32][33][34][35][36] and the calculation parameters [18,24,29] Figure 8 shows the temperature field and the internal gas pressure distribution in the composite along the thickness direction with a laser irradiation time of 1 ms (1 pulse duration).…”
Section: Simulation Of the Internal Gas Pressurementioning
confidence: 99%
See 2 more Smart Citations